Proteomic and metabolomic studies on chilling injury in peach and nectarine - Lurie, Susan (Frontiers in Plant Science, 2022)
Peaches and nectarines are temperate climate stone fruits, which should be stored at 0°C to prevent the ripening of these climacteric fruits. However, if stored for too long or if stored at a higher temperature (4 or 5°C), they develop chilling injury. Chilling injury damage includes (1) dry, mealy, wooly (lack of juice) fruits, (2) hard-textured fruits with no juice (leatheriness), (3) flesh browning, and (4) flesh bleeding or internal reddening. There are genetic components to these disorders in that early season fruits are generally more resistant than late season fruits, and white-fleshed fruits are more susceptible to internal browning than yellow-fleshed fruits. A recent review covered the recent research in genomic and transcriptomic studies, and this review examines findings from proteomic and metabolomics studies. Proteomic studies found that the ethylene synthesis proteins are decreased in cold compromised fruits, and this affects the processes initiated by ethylene including cell wall and volatile changes. Enzymes in metabolic pathways were both higher and lower in abundance in CI fruits, an indication of an imbalance in energy production. Stress proteins increased in both fruits with or without CI, but were higher in damaged fruits. Metabolomics showed the role of levels of sugars, sucrose, raffinose, galactinol, and glucose-6-phosphate in protection against chilling injury, along with other membrane stabilizers such as polyamines. Amino acid changes were inconsistent among the studies. Lipid species changes during storage could be correlated with sensitivity or resistance to CI, but more studies are needed.